Effect of pulsed electric field and pulsed light pre-treatment on the extraction of steroidal alkaloids from potato peels. (May 2015) - Hossain, Mohammad B.; Aguiló-Aguayo, Ingrid; Lyng, James G.; Brunton, Nigel P.; Rai, Dilip K.
Abstract: Pre-treatment of potato peel peels with pulsed electric fields (PEFs) and pulsed lights (PLs) followed by solid –liquid extraction (SLE) with methanol had a pronounced effect on the yield of the steroidal alkaloids in comparison to SLE with no pre-treatment. A PEF pre-treatment field strength of 0.75 kV/cm and 600 μs of treatment time resulted in the maximum yield of total steroidal alkaloids (1856.2 μg/g dried potato peels). This was 99.9% higher than that of the untreated peels whilst field strengths greater than 0.75 kV/cm had a reduced the recoveries of steroidal alkaloids (glycoalkaloids and aglycone alkaloids) for treatment times in the range of 150 to 1500 μs. PL treatments also increased levels of glycoalkaloids and aglycone alkaloids in the potato peels reaching the maximums at fluences of 7.86 J/cm 2 and 9.38 J/cm 2 respectively. However PEF treatment resulted in greater increases in extraction yield than the PL treated peels. Industrial relevance: Steroidal alkaloids, consist of a triterpenoid skeleton, are generally considered to be possible precursors for the production of hormones, antibiotics, and anticancer drugs. Potato peels are excellent untapped sources of these compounds. However, maximisation of extraction of these compounds is crucial for the utilisation of potato peel alkaloids for an emerging phyto-pharmaceutical industry. Pulsed electric field assisted extraction is a quick, cheap, efficient and environment friendly technique which would help maximising the extraction of potato steroidal alkaloids. Pre-treatment of potato peels with pulsed light would further enhance the level of steroidal alkaloids as a stress response. A combined approach of pre-treatment with pulsed light and pulsed electric field in conjunction with large scale solid–liquid extraction could be useful for the industry in obtaining large quantity of starting material, i.e. steroidal alkaloids in order to get high value phyto-pharmaceutical products. Highlights: Pulsed electric field (PEF) treatment enhanced the extraction of potato peel steroidal alkaloids. Pulsed light (PL) treatment increased the initial level of steroidal alkaloids in potato peels. PEF has higher effect in extracting steroidal alkaloids than PL. Solid–liquid extraction in conjunction with PEF and PL would be useful for the industry.